1983
DOI: 10.1007/bf02498725
|View full text |Cite
|
Sign up to set email alerts
|

Proximal osteotomy of the tibia in the treatment of osteoarthritis of the knee

Abstract: A total of 50 patients with osteoarthritis of the knee joint treated by proximal osteotomy of the tibia were followed up 1-5 years after operation. Fusion occurred within an average of 24 weeks. The subjective result of the treatment was good or fair in 44/50 patients. The results were the same 1-2 years and 4-5 years postoperatively. Half the patients showed some significant general disease, most usually hypertension or cardiac disease. Although the patients' subjective condition was significantly better afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…One study that reported a RTW rate of 41.4% evaluated 29 patients between 1972 and 1977 who underwent PTO with a Charnley’s compression device or plaster. 19 The second study found an RTW rate of 51.2% in 43 patients who were treated with the opening wedge hemicallotasis technique, but the authors noted that the 21 patients who did not RTW reported that they retired without listing reasons. 47 The final study evaluated a military population of 181 patients who underwent opening wedge PTO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study that reported a RTW rate of 41.4% evaluated 29 patients between 1972 and 1977 who underwent PTO with a Charnley’s compression device or plaster. 19 The second study found an RTW rate of 51.2% in 43 patients who were treated with the opening wedge hemicallotasis technique, but the authors noted that the 21 patients who did not RTW reported that they retired without listing reasons. 47 The final study evaluated a military population of 181 patients who underwent opening wedge PTO.…”
Section: Resultsmentioning
confidence: 99%
“…A further 2 studies (22.2%) provided information on postoperative RTW level after opening wedge PTO equating to 210 patients. 19,45 Of these, 1 study noted that of the 12 patients who returned to work, a total of 10 (83.3%) returned to work at the same or higher level. 1 The second study reported that 77 (42.5%) patients returned to the same or higher level postoperatively.…”
Section: Resultsmentioning
confidence: 99%